Análise da biodeterioração de sistemas de fachadas e a eficácia de tintas na inibição do desenvolvimento fúngico - Labres, Henrique Santos (Universidade do Vale do Rio dos Sinos, 2019)
Among the mechanisms that affect durability of buildings, there is the biodeterioration by the action of microorganisms, which compromises their elements and devalues aesthetically the constructions, besides being harmful to human health. Thus, it is necessary to find viable solutions especially for the treatment of facades which can extend their life cycle. The use of biocides in paints for coatings film preservation has been applied to meet these requirements, since the fungi colonize the substrates contributing to the surface deterioration and formation of dark pigmented biofilms. The present study aimed to evaluate the facades north and south of two buildings and identify the abundance and richness of fungi and their harmful effects on coatings. Therefore, six biofilm sampling were extracted to evaluate the original conditions of the façades, the efficacy of the cleaning and disinfection procedure, and the painting with two acrylic paints, A and B (indicated for the fight against fungi and bacteria). The following fungi were identified throughout these investigations: Acremonium sp., Alternaria sp., Aspergillus sp., Beauveria sp., Chaetomium sp., Cladophialophora sp., Cladosporium sp., Curvularia sp., Fusarium sp., Nigrospora sp., Penicillium sp., Tripospermum sp. and Mycelia sterilia It was concluded that the paint B obtained best performance than paint A in terms of abundance, however it was showing sensibility to seven genera of fungi, and the paint A, only to four. On the coating surfaces analysis by microscopy were observed biofilm formation, spore deposition, mycelial anchorage and fungal growth between layers films that promoted the adhesion loss of the paintings.
Keywords: Sistemas de fachadas; Durabilidade; Tintas; Fungos; Biodeterioração; Facade; Durability; Fungi; Paints; Biodeterioratio; ACCNPQ::Engenharias::Engenharia Civil